Cross-Cultural Adaptation on Community Culture of Moslem Walesi Mountain in Jayapura City - Tatik Nuryanti (Nusantara Science and Technology Proceedings)
Dichotomy distinguishes mountain communities and coastal communities resulting in their treatment and a different assessment of the society living in the mountainous region. Mountainous communities among Papuans have been stereotyped as a tough community, a source of conflict and a lagging society. This resulted in the mountainous community more difficult to be accepted by other communities when it comes out of its territory. This study would like to express how intercultural adaptation process Walesi Moslem mountains community in the City of Jayapura.Using the Theory of Intercultural Adaptation proposed by Kim stating that all individuals when entering a new cultural culture and unfamiliar then he will become a stranger and require the process of adaptation.This research is a qualitative research with the research subject is the Walesi Moslem mountain community that has been at least for five years living in the City of Jayapura.The results showed that the Walesi Moslem peoples when entering the city of Jayapura initially experienced difficulties because of the high bonds of brotherhood among them that tend to be closed to the society and other cultures. The interesting thing in this research is that the Muslim identity makes it easy for the Walesi Moslem peoples to be accepted by the immigrant and coastal communities in the City of Jayapura.